Peningkatan Hasil Belajar Geografi Siswa Menggunakan Model Pembelajaran Kooperatif Tipe Picture And Picture - Fenny Endrayani; La Ode Amaluddin; La Ode Mursalam; Rahma Musyawarah; Syukri Nyompa (Universitas Negeri Makassar, 2019)
SMAN 2 BauBau is one of the schools in BauBau City that is the object of research because the learning outcomes are still low, this is because only 62.5% of the tests that meet the KKM. The objectives of this study are: (1) To increase student learning activities in class XI IPS2 of SMAN 2 BauBau which are taught through the application of cooperative learning models of Picture and Picture types on flora and fauna material in Indonesia and the world. (2) To increase the teaching activities of teachers in class XI IPS2 SMAN 2 BauBau taught through the application of cooperative learning models Picture and Picture types on flora and fauna in Indonesia and the world Picture and Picture type on flora and fauna material in Indonesia and the world. Data about student learning activities and teacher teaching activities were obtained through observation sheets, while student geography learning outcomes data were obtained through learning outcomes tests, (cycles). The results showed: (1) Student activities with the application of the Contextual Approach learning model in cycle I amounted to 2.4 which included in the sufficient category, increased in cycle II to 3.7 which included in the category of good; (2) The teaching activities of the first cycle teachers mean the average score of the activities of the teachers is 2.8 which is included in the sufficient category and increased in the second cycle to 3.6 which is categorized as good; (3) There is an increase in the learning outcomes of class XI IPS-2 SMAN 2 BauBau after applying the Cooperative Learning model of the Picture and picture type. Where in the first cycle that is obtained 62.5% student mastery learning and in cycle II student learning completeness increased to 87.5%.SMAN 2 BauBau adalah salah satu sekolah di Kota BauBau yang menjadi objek peneliti karena hasil belajarnya masih rendah, hal ini dikarenakan hanya 62,5% hasil ulangan yang memenuhi KKM. Tujuan penelitian ini adalah: (1) Untuk meningkatkan aktivitas belajar siswa di kelas XI IPS2 SMAN 2 BauBau yang diajar melalui penerapan model pembelajaran kooperatif tipe Picture and Picture pada materi flora dan fauna di indonesia dan dunia.(2)Untuk meningkatkan aktivitas mengajar guru di kelas XI IPS2 SMAN 2 BauBau yang diajar melalui penerapan model pembelajaran kooperatif tipe Picture and Picture pada materi flora dan fauna di indonesia dan dunia.(3)Untuk mengetahui peningkatan hasil belajar siswa di kelas XI IPS2 SMAN 2 BauBau yang diajar melalui penerapan model pembelajaran kooperatif tipe Picture and Picture pada materi flora dan fauna di indonesia dan dunia. Data tentang aktivitas belajar siswa dan aktivitas mengajar guru diperoleh melalui lembaran observasi, sedangkan data hasil belajar geografi siswa diperoleh melalui tes hasil belajar, (siklus). Hasil penelitian menunjukan: (1) Aktivitas siswa dengan penerapan model pembelajaran Pendekatan Kontekstual pada siklus I sebesar 2,4 yang termasuk pada kategori cukup, meningkat pada siklus II menjadi 3,7 yang termasuk pada katergori baik; (2) Aktivitas mengajar guru siklus I skor rata-rata aktivitas guru adalah 2,8 yang termasuk kategori cukup dan meningkat pada siklus II menjadi 3,6 yang berkategori baik; (3) Ada peningkatan hasil belajar geografi kelas XI IPS-2 SMAN 2 BauBau setelah menerapkan model Pembelajaran Kooperatif tipe Picture and picture. Dimana pada siklus I yaitu diperoleh ketuntasan belajar siswa 62,5% dan pada siklus II ketuntasan belajar siswa meningkat menjadi 87,5%.